Evaluación de la gestión administrativa del departamento de cartera vencida de la EMAARS-EP Parroquia Ángel Pedro Giler del Cantón Tosagua. - Laaz López, Gabriela Guadalupe (2018)
The purpose of this study was to evaluate the efficiency of the administrators of the Expired Portfolio Department of the EMAARS-EP of Tosagua canton. For this the interview was carried out to the department Director to know in the first instance which are the processes of the area, likewise the technique of observation was applied, which allowed to observe facts and present social realities according to the activities that perform. In addition, methods such as the inductive were immersed which allowed going from the particular to the general in the information gathered through the bibliography research, the same that facilitated the sources of the document, and the deductive method helped to obtain an approach of the processes that they are made in the institution; the efficiency of the administrative staff was determined through field research and performance evaluation, the analytical method and the synthetic method were applied, the same ones that allowed the collection and analysis of the evaluations made to the administrative staff, giving as results, deficient training to the personnel that works in the marketing department and inconveniences with the issuance of electronic invoices. Based on what has been described, an improvement plan is proposed which includes the strategies, activities and tasks with the compliance times in order to improve the efficiency of the Past Due Portfolio department. It is concluded that the Past Due Portfolio department does not reach the maximum efficiency percentage.